2016
DOI: 10.1590/1983-084x/15_007
|View full text |Cite
|
Sign up to set email alerts
|

Técnicas de conservação pós-colheita para o manjericão

Abstract: RESUMO:O trabalho teve como objetivo avaliar a qualidade e vida útil de ramos de manjericão submetidos a procedimentos de conservação pós-colheita. O experimento foi conduzido no Laboratório de Plantas Medicinais do Departamento de Horticultura, da Universidade Estadual Júlio de Mesquita Filho, município de Botucatu, São Paulo. O delineamento utilizado foi inteiramente casualizado com quatro tratamentos e seis repetições. Os tratamentos consistiram de técnicas de conservação pós-colheita seguintes: Testemunha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Studies that evaluated the effect of hydrocooling on some leafy vegetables showed satisfactory results, which showed delayed visual wilting, increased shelf life and reduced water loss in lettuce leaves (França et al, 2015), welsh onion (Travassos et al, 2017) and basil (Teixeira et al, 2016). However, this information for arugula crop is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that evaluated the effect of hydrocooling on some leafy vegetables showed satisfactory results, which showed delayed visual wilting, increased shelf life and reduced water loss in lettuce leaves (França et al, 2015), welsh onion (Travassos et al, 2017) and basil (Teixeira et al, 2016). However, this information for arugula crop is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Postharvest loss control methods are employed to slow or minimize deterioration processes of the products through different storage methods, transport, and treatment techniques, and hydrocooling is an advantageous method for fresh vegetables (Teixeira et al, 2016). This study aimed to evaluate the hydrocooling efficiency when associated with the storage period in the postharvest shelf life of arugula leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Produtos insensíveis ao excesso de umidade, ou que não tem suas características influenciadas pelas mesmas, como por exemplo: melão, kiwi, alho-poró, espinafre, milho, entre outros, inclusive a cebolinha, podem utilizar o método de hidroresfriamento comágua refrigerada como alternativa de tratamento pós-colheita, que se destaca entre várias técnicas por sua simplicidade, praticidade, eficiência e baixo custo (Kanlayanarat & Acedo, 2009). O método do hidroresfriamento, que consiste na aspersão deágua sobre o produto, ou imersão do mesmo emágua gelada (mistura deágua e gelo), logo após a sua retirada do campo e antes de realizar a sua embalagem, armazenagem e/ou distribuição se apresenta como uma boa alternativa (simples, eficiente e de baixo custo) na conservação de produtos hortícolas, pois reduz o calor de campo e diminui os processos metabólicos, responsáveis pela senescência, reduzindo também a perda de umidade (Teixeira, et al, 2016). Entretanto, segundo Silva et al (2015), em relaçãoàs cebolinhas, são poucos os trabalhos encontrados na literatura dedicados a avaliar suas qualidades físico-químicas, estabilidade do produto, ou até mesmo sobre os tratamentos pós-colheita.…”
Section: Introductionunclassified
“…Post-harvest quality refers to the set of characteristics that differentiate individual units of a product, being significant to determine the product acceptability degree by the buyer. In order to meet this demanding market, agricultural production must aim to produce quality food, with high nutritional value and higher post-harvest conservation (Yuri, 2004, Chitarra & Chitarra, 2005, Teixeira et al, 2016. In this respect, agriculture is an expressive activity for Brazil, which has high production as a remarkable characteristic.…”
Section: Introductionmentioning
confidence: 99%